FACTORS ASSOCIATED WITH WASTE MANAGEMENT IN THE COMMUNITY IN PALMERAH SUB-DISTRICT, JAMBI CITY - Rini, Willia Novita Eka; Butar Butar, Marta; Lesmana, Oka; Sumiyarsih, Sumiyarsih (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Backgrounds: Garbage is produced by human activities which if not managed properly will have an impact on environmental hygiene. Paal Merah sub-district is a sub-district in Jambi City with a dense population. Based on data from the Jambi City Environmental Service, the amount of waste generated in the Paal Merah sub-district has increased from year to year. Objective: The purpose of this study was to determine the factors related to the behavior of waste management in the community in Paal Merah District, Jambi City. Methods: The study was conducted using a cross-sectional design with a sample size of 105 respondents. Results: The results of this study are that there is a relationship between lack of knowledge (p-value 0.044 PR 2.01 95% CI 1.01-4.00), attitude (p-value 0.45 PR 1.63 95% CI 1.11-2 .40), subjective norm (p-value 0.027 PR 1.65 95%CI 1.08-2.52), control of behavior (p-value 0.004 PR 1.92 95%CI 1.33-2.77) with poor waste management. Conclusion: Suggestions for the government to provide facilities and infrastructure and increase socialization about waste management so as to increase control over community behavior in managing waste.